Fuzzy clustering of multi-view relational data with pairwise constraints - Branco, Diogo P. P.; de A T de Carvalho, Francisco (IEEE International Fuzzy Systems conference proceedings, 2017)
Thvs paper presents SS-MVFCVSMdd, a semi-supervised multiview fuzzy clustering algorithm for relational data described by multiple dissimilarity matrices. SS-MVFCVSMdd provides a fuzzy partition in a predetermined number of fuzzy clusters, a representative for each fuzzy cluster, learns a relevance weight for each dissimilarity matrix, and takes into account pairwise constraints must-link and cannot-link, by optimizing a suitable objective function. Experiments with multiview real-valued data sets described by multiple dissimilarity matrices show the usefulness of the proposed algorithm.